You are on page 1of 5

28 2002

:

1
. . vi xi,
i=1, 2, , k,
xi .
. fi xi,
i=1, 2, , k, vi
, , f i =
. ) f i =

vi
, i=1, 2, , k.
v

vi
, 0viv,
v

vi v
 0 f i 1 , i=1, 2, , k .
v v
v
v
v
v + v + ... + v k v
) f1 + f 2 + ... + f k = 1 + 2 + ... + k = 1 2
= = 1.
v
v
v
v
v

1. , , :
=, : ()=0.
: ()=()+()-(), ()=()+().
2. .
.
( )
(()),
(()), (()), ,
P ( A) =

N ( A)
=
.
N ( )

. :
()=1 ()=0.
2
. f ( x ) =

2x
x+10  x-1,
x +1

=-{-1}.
2x
23 6 3
=
= = .
x 3 x + 1 3 + 1
4 2

. lim f ( x ) = lim
x 3

2x
=-{-1},
x +1
2( x + 1) 2x
2x + 2 2 x
2
f( x ) =
 f( x ) =
 f( x ) =
.
2
2
( x + 1)
( x + 1)
( x + 1) 2

. f ( x ) =

. (x0, f(x0)) .
y=2x+5,
:
f(x0)=  f(x0)=2 

2
( x 0 + 1)

= 2  (x0+1) =1  x0+1=1 

 x0+1=1 x0+1= - 1  x0=0 x0= - 2.


1
=+
=2, =2+.
x0=0, f (0) =

20
= 0 , ,
0 +1

(0,0) 0=20+  =0,


=2.

x0= - 2, f (2) =

2 ( 2)
= 4 , ,
2 +1

(-2,4) 4=2(-2)+ 
 4=-4+  =8,
=2+8.
2
 x0=0, f (0) =

2
20
= 0 f(0) =
= 2 ,
0 +1
(0 + 1) 2

y-f(x0)=f(x0)(x-x0) 
 y-f(0)=f(0)(x-0)  y-0=2(x-0)  y=2x.

 x0= - 2, f (2) =

2
2 ( 2)
= 4 f(2) =
= 2 ,
2 +1
(2 + 1) 2

y-f(x0)=f(x0)(x-x0) 
 y-f(-2)=f(-2)(x+2)  y-4=2(x+2)  y=2x+8.

3
xi
vi

xivi

8
9
10
13
14
15
16
18

8
9
10
26
28
15
16
18
130

1
1
1
2
2
1
1
1
10
k

__

. x =

-5
-4
-3
0
1
2
3
5
-

25
16
9
0
1
4
9
25
-

x i vi
=

__

xi x

__

x i x vi

25
16
9
0
2
4
9
25
90

x i vi
i =1

__

xi x

i =1

130
= 13
10

10

,
,
.
: x5=13 x6 =14, =

x 5 + x 6 13 + 14 27
=
=
= 13,5 .
2
2
2

, 2
, 0=13 0=14.
. To R : R=18-8=10.
2

__

xi x vi

90

s x2 = i=1
=
=9,
v
10
k

: sx=3.
: CVx =

sx
__

3
.
13

. xi 10%, yi= xi-10% xi 


 yi= xi-0,1 xi  yi= 0,9xi.

, x, y c, y=cx, :
__

__

y = c x

s y =| c | s x , s y , s x
y x.
:

__

CV y =

__

y = 0,9 x

sy
__

0,9 s x
__

0,9 x

s y = 0,9 s x ,

s
= x = CV x .
__

x
3

4
. 1
:
()=()+()-()  ()+()=()+() .
: ()+()2() 
 ()+()2()  ()().
2
()=()  ()+()-() = () 
 ()+()=2(), , ()().
. f(x)=(x-P(AB))3-(x-P(AB))3
, f(x)=3(x-P(AB))2-3(x-P(AB))2 
 f(x)=3[(x-P(AB))2-(x-P(AB))2] 
 f(x)=3[x-P(AB)+x-P(AB)][x-P(AB)-x+P(AB)] 
 f(x)=3[2x-P(AB)-P(AB)][P(AB)-P(AB)] .
:
(AB)(AB), P(AB)P(AB)  P(AB)-P(AB)0,
()(), P(AB)-P(AB)<0.
:
 f(x)>0  3[2x-P(AB)-P(AB)][P(AB)-P(AB)]>0 
 2x-P(AB)-P(AB)<0  x <
 x<

P ( A) + P ( B )
.
2

P(A B) + P(A B)

2

f ,
x<

P ( A) + P ( B )
.
2

 f(x)<0  3[2x-P(AB)-P(AB)][P(AB)-P(AB)]<0 
 2x-P(AB)-P(AB)>0  x >
 x>

P ( A) + P ( B )
.
2

P(A B) + P(A B)

2

f ,
x>

P ( A) + P ( B )
.
2

 f
x=

P ( A) + P ( B )
.
2

. , , : =,
: ()=0 ()=()+().
: f(x)=(x-P(AB))3-(x-0)3  f(x)=(x-P(AB))3-x3 .
4

:
 f(())=(()-P(AB))3-(())3  f(())=(-())3-(())3
 f(()) = -(())3-(())3 (),
()=()+()  -() = ()- ().

3
 f(())=(()-P(AB)) -(())3  f(())=(-())3-(())3
 f(()) = -(())3-(())3 (),
()=()+()  -() = ()- ().
() () : f(())= f(()).